Dosimetric utility of structural changes in gamma irradiated graphite-rich pencils - Sani, S.F. A.; Ismail, S.S.; Almugren, K.S.; Khandaker, Mayeen Uddin *; Bradley, D.A. * (Elsevier, 2020)
9B and H grade carbon-based pencil (carbon concentrations approaching 81 and 62 wt respectively %) have been investigated for radiotherapy dosimetry applications, offering low dependence on photon energy and near soft tissue effective atomic number. Comparison has been made with highly oriented pyrolytic graphite (HOPG), a pure and ordered synthetic form of graphite. The samples were exposed to 60Co gamma ray doses from 0 to 20 Gy (encompassing the range of doses utilized in fractionated radiotherapy), structural interaction alterations resulting from the radiation doses being observed via Raman and Photoluminescence (PL) spectroscopy and X-ray diffraction (XRD). Among the most prominent features to be observed in Raman spectra are the so-called G and D peaks, appearing at 1578 cm−1 and 1348 cm−1 respectively. The intensity ratio ID/IG was used for further characterization of the dose-dependent defects produced in the graphitic materials. From PL measurement, sample average energy band gap values are observed to be within the region 1.114–1.116 eV, being considered direct bandgap-like semiconductors. The characteristic XRD crystal plane Miller index (002) peak was observed in order to calculate the atomic spacing, lattice constant and the degree of structural order of the irradiated samples.